Multiple retinal pigment epithelial detachments: what should we do? A propos of an idiopathic case - Blanco-Domínguez,Irene (2020)
Abstract The purpose is to report the management of multiple retinal epithelial detachments (PEDs) in a 50-year-old male with bilateral PEDs not associated with chorioretinal or systemic pathologies after a complete study. Idiopathic multiple PEDs could be a variation of central serous chorioretinopathy, but other causes as well as other pathological conditions which could produce similar images, are required to be ruled out.